Effect of additives on a surface textured piston ring–cylinder liner system. (3rd April 2019) - Mishra, Parul; Ramkumar, P.
ABSTRACT: Laser texturing of the surface is a known approach to improve the tribological performance of mechanical systems. Many studies focused on optimising surface texture parameters for the piston-ring cylinder liner (PRCL) system. However, little attention is given to explore the effect of the textured surface on additive film formation. In the present work, the effect of a laser textured surface on the formation of additives tribochemical films and its impact on the tribological performance of PRCL system is studied. Commercially available steel piston ring and grey cast iron cylinder liner are used as samples to carry out the experiments using linear reciprocating tribometer. Experiments are carried out at 75 N load, 0.1 Hz frequency and 80°C temperature, using polyalphaolefin as base oil mixed with different additives. It is found that dimples are interfering in the formation of tribo-chemical films. However, the hydrodynamic effect of dimples is contributing to the improvement of lubrication performance even in the presence of additives.